The Impact of Intra-articular Depot Betamethasone Injection on Insulin Resistance Among Diabetic Patients With Osteoarthritis of the Knee: A Case-Control Study. Issue 4 (June 2018) - Habib, George; Chernin, Mark; Sakas, Fahed; Artul, Suheil; Jabbour, Adel; Jabaly-Habib, Haneen
Abstract : Objective: The aim of this study was to evaluate the impact of intra-articular corticosteroid injection (IACI) of depot betamethasone at the knee joint on insulin resistance (IR). Methods: Patients with type 2 diabetes, non–insulin treated, with painful osteoarthritis of the knee were requested to participate in our study. After consent, demographic, clinical, and laboratory parameters were documented in addition to fasting blood glucose (FBG) and fasting blood insulin levels just prior to IACI of 1 mL of depot betamethasone. Fasting blood glucose and fasting blood insulin levels were repeated the next day following the IACI and 8 days later. Age- and sex-matched group of patients with type 2 diabetes from the same clinic were recruited as a control group (case-control study). Insulin resistance was calculated using Homeostasis Model Assessment–Insulin Resistance. Mann-Whitney U test, χ 2 test, and Wilcoxon signed rank tests were used for statistical analysis. Results: Eleven patients were recruited in the patients' group and 10 patients in the control group. Median FBG in the patients' group at baseline was 148 ± 51 mg/dL, and median IR was 5.12 ± 2.46. One day following the IACI, median FBG level was 247 ± 104 mg/dL ( P = 0.004, compared with baseline), with median IR of 20.8 ± 7.01 ( P = 0.0039). The median ratios of blood glucose and IR 1 day following the IACI compared with baseline were 1.7 and 4.1, respectively. Eight days following the IACI, mean FBG and IR levels were not significantly different from baseline. Conclusions: Intra-articular corticosteroid injection of betamethasone at the knee joint among patients with diabetes was associated with a significant increase in IR levels compared with baseline levels, 1 day following the injection. The mean percentage of increase in IR was higher than that for FBG levels.